Analysis of intense rains aiming to dimension soil conservation structures for Chapecó region, SC - Back, Álvaro José (2019)
Mechanical practices or hydraulic works are part of the principles of the conservationist management of soil and are tailored depending on several factors, among them the characteristics of the local rainfall. This work aims to analyze the data of heavy rain to support the dimensioning of soil conservation projects in the region of Chapecó, Santa Catarina. The historical series data of daily precipitation obtained in Chapecó rainfall station was used. The parameters of the Gumbel-Chow distribution were adjusted based on the historical series of maximum annual rainfall for the period from 1973 to 2016. From the breakdown of the maximum daily rainfall, the intense rainfall equation was adjusted. It was noted that there is a higher frequency of extreme rainfall events in autumn and a lower one during summer. The maximum daily rainfall, with a return period of 10 years, to be adopted as a criterion for level terracing dimensioning was 146.9mm. For drainage terraces, the maximum rainfall intensity lasting 15 minutes and with a return period of 10 years was assumed to be 141.9mm h-1.